2022
DOI: 10.3390/toxins14040266
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Fumonisins by the Consecutive Action of a Fusion Enzyme

Abstract: Fumonisins (FBs) are toxic mycotoxins that commonly exist in food and feed. FBs can induce many aspects of toxicity, leading to adverse effects on human and animal health; therefore, investigating methods to reduce fumonisin contamination is necessary. In our study, we generated a recombinant fusion enzyme called FUMDI by linking the carboxylesterase gene (fumD) and the aminotransferase gene (fumI) by overlapping polymerase chain reaction (PCR). The fusion enzyme FUMDI was successfully, secretively expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(59 reference statements)
0
2
0
1
Order By: Relevance
“…Because the detoxification of FB 1 requires the sequential action of carboxylesterases and aminotransferases, Kailin Li generated the fusion enzyme FUMDI by connecting the carboxylesterase gene (fumD) with the aminotransferase gene (fumI) through PCR. Researchers subsequently expressed the enzyme in P. pastoris , in which it almost completely degraded 5 μg/mL FB 1 in 24 h. The experiments demonstrated that the fusion enzyme FUMDI and its degradation products were not toxic to human gastric epithelial cells ( Li K. et al, 2022 ). The detoxification enzymes of FB 1 are summarized in Table 6 .…”
Section: Common Mycotoxins and Corresponding Enzymes Used For Detoxif...mentioning
confidence: 99%
“…Because the detoxification of FB 1 requires the sequential action of carboxylesterases and aminotransferases, Kailin Li generated the fusion enzyme FUMDI by connecting the carboxylesterase gene (fumD) with the aminotransferase gene (fumI) through PCR. Researchers subsequently expressed the enzyme in P. pastoris , in which it almost completely degraded 5 μg/mL FB 1 in 24 h. The experiments demonstrated that the fusion enzyme FUMDI and its degradation products were not toxic to human gastric epithelial cells ( Li K. et al, 2022 ). The detoxification enzymes of FB 1 are summarized in Table 6 .…”
Section: Common Mycotoxins and Corresponding Enzymes Used For Detoxif...mentioning
confidence: 99%
“…Fused enzymes . An interesting study describing a fusion enzyme of carboxylesterase and aminotransferase for FB1 degradation was published in 2021 [ 153 ]. The authors of this study designed, constructed, and expressed a recombinant fusion enzyme called FUMDI by linking the carboxylesterase gene ( fumD ) and the aminotransferase gene ( fumI ) by overlapping polymerase chain reaction (PCR).…”
Section: Biotransformation Of Fumonisin B1mentioning
confidence: 99%
“…At the same time, a new effective approach has recently appeared, which can be used to create multi-functional fused enzymes with an extended substrate range. A FUMDI enzyme combined the properties of the carboxylesterase FumD and aminotransferase FumI and provided irreversible degradation of FB1, FB2, and FB3 [ 153 ]. A ZPF1 enzyme with the ability to degrade AFB1 and ZEN was constructed via the linking of mutant V153H of ZHD101 and manganese peroxidase [ 160 ].…”
Section: Prospects For Use Of Microbial Destructors Of Fusariotoxins ...mentioning
confidence: 99%
“…Mycotoxins being dangerous natural compounds created by various pathogenic fungus that occur in nature in a variety of products from all over the globe. Food and feed frequently include deadly mycotoxins called fumonisins (FBs), (Li et al, 2022). The potential impacts on the wellbeing of the animals are considered in the threat analysis of mycotoxins in animal feed, together with the potential dangers of their compounds transferring to animal -based foods intended for human consumption (Mackay et al, 2022).…”
Section: Introductionmentioning
confidence: 99%